Social differentiation, farming systems, and agrarian change in rural Ghana - Michael Pervarah (Cogent Social Sciences, 2024)
AbstractAgriculture is predominantly rural and dominated by smallholder farmers. However, efforts to improve smallholder agricultural production have not yielded the desired results. Some scholars and practitioners have argued that development interventions often overlook the variability in smallholder farming systems. Therefore, it is unlikely that such initiatives will directly reach the smallholder end of the landholding spectrum to facilitate desired outcomes. This study examined differences within the smallholder sector in the Kassena Nankana Traditional Area, showing how socioeconomic differentiation among smallholders defines their choice of farming system. Using a mixed methods approach, this study identified three types of farms: compound, lowland, and bush farms, characterized by a differential pattern of traditional farming methods, prevalent in compound farms compared to mechanized farming practices, predominantly in lowland and bush farms. This pattern highlights the production orientation of smallholders and specifies the farming practices they engage in and rationalize to meet household consumption needs and market demand. The study concludes that resource endowments are crucial in determining farm types owned by differentiated smallholders and the farming systems they choose in response to persuasive incentives. Extension services should harness the local farmers’ understanding of soil characteristics and the diversity of farming systems when designing specific strategies to promote productivity-enhancing technologies and practices, to achieve sustainable smallholder transformations in rural Ghana.